Flower Extracts of Cage Plants (Canavalia virosa) as an Indicator of Acid Base - Andi M. Rendi; Supriadi Supriadi; Suherman Suherman (Universitas Tadulako, 2020)
Cage plants (Canavalia virosa) are classified as nuts. This study aims to prove the flowers of the cage plants as acid-base indicators and determine the type of acid-base titration that is suitable for indicators of cage plants. The flowers of the cage plants were macerated with ethanol. Extras were tested as indicators in acid-base solutions, buffer solutions, and compared with phenolphthalein and methyl orange for acid-base titration, namely: strong acid with a strong base, a weak acid with a strong base, and weak base with strong acid. The results obtained in this study, namely: flower extracts of cage plants in strong red acid, in weak acid pink, in strong green bases, and weak bases in light green. In a buffer solution of pH 1 to pH 11, the flower extract of the cage plants gives 4 color groups, namely: a buffer solution with pH 1 colored red, pH 3 colored pink, pH 5 to pH 9 being light green, and pH 11 being dark blue. Cage plant flower extract can be used as an indicator of acid-base, cage plant flower extract can be used on strong-base strong acid titration, strong weak-acid base, and weak-strong base acid titration.